Deuterium‐Stabilized (R)‐Pioglitazone (PXL065) Is Responsible for Pioglitazone Efficacy in NASH yet Exhibits Little to No PPARγ Activity. Issue 8 (10th April 2021) - Jacques, Vincent; Bolze, Sébastien; Hallakou‐Bozec, Sophie; Czarnik, Anthony W.; Divakaruni, Ajit S.; Fouqueray, Pascale; Murphy, Anne N.; Van der Ploeg, Lex H.T.; DeWitt, Sheila
Abstract : The antidiabetic drug pioglitazone is, to date, the most efficacious oral drug recommended off‐label for the treatment of nondiabetic or diabetic patients with biopsy‐proven nonalcoholic steatohepatitis (NASH). However, weight gain and edema side effects have limited its use for NASH. Pioglitazone is a mixture of two stereoisomers (( R )‐pioglitazone and ( S )‐pioglitazone) that interconvert in vitro and in vivo . We aimed to characterize their individual pharmacology to develop a safer and potentially more potent drug for NASH. We stabilized the stereoisomers of pioglitazone with deuterium at the chiral center. Preclinical studies with deuterium‐stabilized ( R )‐pioglitazone (PXL065) and ( S )‐pioglitazone demonstrated that ( R )‐pioglitazone retains the efficacy of pioglitazone in NASH, including reduced hepatic triglycerides, free fatty acids, cholesterol, steatosis, inflammation, hepatocyte enlargement, and fibrosis. Although both stereoisomers inhibit the mitochondrial pyruvate carrier, PXL065 shows limited to no peroxisome proliferator–activated receptor gamma (PPARγ) activity, whereas ( S )‐pioglitazone appears responsible for the PPARγ activity and associated weight gain. Nonetheless, in preclinical models, both stereoisomers reduce plasma glucose and hepatic fibrosis to the same extent as pioglitazone, suggesting that these benefits may also be mediated by altered mitochondrial metabolism. In a phase 1a clinical study, we demonstrated safety and tolerability of single 7.5‐mg, 22.5‐mg, and 30‐mg doses of PXL065 as well as preferential exposure to the ( R )‐stereoisomer in comparison to 45‐mg pioglitazone. Conclusion : PXL065 at a dose lower than 22.5 mg is predicted to exhibit efficacy for NASH equal to, or greater than, 45‐mg pioglitazone without the potentially detrimental weight gain and edema. The development of PXL065 for NASH represents a unique opportunity to leverage the therapeutic benefits of pioglitazone, while reducing or eliminating PPARγ‐related side effects. Abstract : image